Review of the Clinical Studies Using the 21-Gene Assay - Kelly, Catherine M. (AlphaMed Press, 2010)
PURPOSE. A major challenge in treating early-stage hormone receptor (HR)(+) breast cancer is selecting women who, after initial surgery, do not require chemotherapy. Better prognostic and predictive tests are needed. The 21-gene assay is the only widely commercially available gene signature that can be performed on formalin-fixed paraffin-embedded tissue. METHODS. We conducted a review of the literature supporting the prognostic and predictive ability of the 21-gene assay in HR(+) node-negative and node-positive breast cancer patients in chemotherapy-/endocrine-treated and untreated populations. We considered: (a) How accurate is the recurrence score (RS) as a prognostic factor for distant recurrence? (b) How accurate is the RS as a predictive factor for benefit from systemic therapy? (c) How does the RS compare with other prognostic/predictive factors such as tumor size, tumor grade, patient age, and integrated decision aids such as Adjuvant! Online? (d) How do patients and physicians view the 21-gene assay? (e) What are the cost implications of the 21-gene assay? RESULTS. The 21-gene assay: (a) provided accurate risk information; (b) predicted response to cyclophosphamide, methotrexate, and 5-fluorouracil and to cyclophosphamide, doxorubicin, and 5-fluorouracil chemotherapy; (c) added additional information to traditional biomarkers; (d) was viewed positively by both physicians and patients; and (e) fell within the cost-effectiveness values in North America. CONCLUSION. This assay may be offered to patients with node-negative HR(+) breast cancer to assist in adjuvant treatment decisions. Data are accumulating to support the use of the 21-gene assay in HR(+) node-positive patients.